One flew over the cuckoo's nest - Kesey, Ken 1935- (New York Penguin Books, 1999)
McMurphy, a criminal who feigns insanity, is admitted to a mental hospital where he challenges the autocratic authority of the head nurse.
First published in the United States of America by The Viking Press 1962.